2021
DOI: 10.3390/ijerph181910223
|View full text |Cite
|
Sign up to set email alerts
|

Lipoedema as a Social Problem. A Scoping Review

Abstract: (1) Background: Lipoedema is a disease characterized by excessive bilateral and symmetrical accumulation of subcutaneous tissue in the lower extremities. It is a poorly understood condition, and low awareness of its existence often leads to incorrect diagnosis Initially, lipoedema was considered to be completely independent of lifestyle Currently, however, more and more cases of the coexistence of lipoedema and obesity are described in the literature as additionally affecting the severity of the disease The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, a large proportion of lipoedema patients is thought to also to be obese [ 35 ]. Dudek et al in their study of 329 lipoedema patients, only 4.3% of subjects had normal body weight while obesity was present in 81.3% of patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a large proportion of lipoedema patients is thought to also to be obese [ 35 ]. Dudek et al in their study of 329 lipoedema patients, only 4.3% of subjects had normal body weight while obesity was present in 81.3% of patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various types of scales and questionnaires are beneficial in indicating the improvement of patients’ health status [ 40 ]. Decreasing the level of pain and severity of symptoms, increasing the quality of life and increasing functionality are very important therapeutic goals, and the evaluation of therapy methods by means of these tools could indicate the most successful treatment for patients [ 31 , 35 , 38 ]. Five outcome instruments: the Short Form 36 (SF-36), the lymphedema-specific Freiburg Quality of Life Assessment for Lymphatic Disorders (FLQA-lk), the Knee Outcome Survey Activities of Daily Living Scale (KOS-ADL), the Symptom Checklist-90-revised (SCL-90R) and the Six-Minute Walk Test were evaluated in 96 lipoedema and 107 lymphoedema patients in a study by Angst et al The results showed that all the tools used have favourable features in the specific assessment of lipoedema and lymphoedema, and can be successfully used in the assessment of therapeutic outcomes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, some women with lipedema may also have additional areas of localized adiposity [ 94 ], making the diagnosis even more challenging. As there have not been many randomized controlled trials addressing lipedema as a social issue, research has tended to rely on patient-completed surveys, which are not objective [ 185 ]. Therefore, additional research should be conducted to advance our understanding of lipedema; create specific diagnostic criteria; and explore the relationships between lipedema, lifestyle, comorbidities, and quality—all of which shorten the time to receive a diagnosis.…”
Section: Current Challenges With Lipedemamentioning
confidence: 99%
“…Although easy bruising is widely reported in lipedema, the exact reason for its existence among lipedema patients has not yet been established [17]. Moreover, lipedema patients also struggle with a lack of understanding, low self-esteem, feeling of hopelessness, and a decreased level of quality of life [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%